Design and investigation of HF-ozonators - Krasnyj, V.V.; Klosovskij, A.V.; Nezovibat’ko, Yu.N.; Pogozhev, D.P.; Taran, V.S.; Shvets, O.M.; Utemov, D.N. (Вопросы атомной науки и техники, 2000)
In the present activity the ozonators with the time modulated power supplies and reactors (plate-type and tubular) operating on the base of surface barrier discharge are investigated. The measurements of the main specifications of the reactor at the average power level up to 50W were performed using spectroscopy diagnostic. The relationships of the output concentration of ozone on the temperature of the reactor, frequency and power of a source, air injection rates were obtained and discussed in detail. In addition, on the basis of the performed experiments the geometrical parameters of reactors were optimized. Some types of reactors and power supplies with the power up to 500W were designed. The prototypes of ozonators for medical purposes, agriculture and household applications have been manufactured.